PUBLIC POLICY APPROACH TO DISASTER RISK ANTICIPATION STRATEGIES IN CIVIL ENGINEERING STUDIES IN INDONESIA - B.M.A.S. Anaconda Bangkara; Henry Kristian Siburian; Ani Heryani; Adi Mursalin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
This study described a public policy approach to anticipate the impact of natural disasters in Indonesia's civil engineering context. Many studies have reported how public policy approaches anticipate and manage disaster risk strategies. However, few relate to the role of civil engineering, especially the younger generation involved in designing policies and playing their role in natural disaster management. This study has reviewed 50 disaster papers that we analyzed with a phenomenological approach to understanding the role and approach of public policy in dealing with disaster hazards and risks. Our Monalisa system involves data coding, in-depth evaluation, and impotence of data to get the most answers. After a series of studies and discussions, we can conclude that the disaster management policy was originally a policy designed by the state and then directed to the National Disaster Management Agency following presidential regulations so that the law was made an effort to cope with disasters and be responsible to the state. The relationship between civil engineering is that they participate in policy and impact analysis studies closely related to public and private development. We hope that these findings will become an essential friend for further studies.